Analisis Trend Produksi Padi Sawah Daerah Sentra Bosowa (Bone, Soppeng, Wajo) Terhadap Produksi Padi Sawah di Sulawesi Selatan - Atira Atira; Arifin Arifin; Mohammad Anwar Sadat (Jurnal Agribis, 2021)
This research was conducted in Bone District, Soppeng, Wajo in South Sulawesi. This location was chosen with the consideration that it has been a long time managing the Paddy Paddy. The data used are: secondary data, namely data obtained from agencies / institutions related to or related to this research. The purpose of this study was to analyze the trend of lowland rice production in the center of Bosowa (Bone, Soppeng, Wajo) on lowland rice production in South Sulawesi. The data that has been collected is then tabulated to obtain real data used for analysis purposes. This study used a quantitative descriptive analysis method to determine the amount of income obtained by farmers from the analysis of lowland rice production trends in the Bosowa area of ​​lowland rice production in South Sulawesi. The results showed that the amount of income obtained by farmers from lowland rice production in the central area of ​​Bosowa was 1,792,509,419 against lowland rice production in South Sulawesi as much as 55,045,131.00. The results of the calculation have been able to produce lowland rice production in the Bosowa center area in South Sulawesi.